A Review of Anti-hyperglycemic Effects of Curry Leaf Tree (Murraya koenigii) - Vinotha Sanmugarajah; Gowri Rajkumar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Diabetes mellitus is becoming a metabolic disease that is defined by the level of hyperglycemia. Nowadays, it has a serious threat to public healthiness in throughout the world. Constituents and extracts isolated from diverse natural resources, mainly plants, have constantly been a rich store for controlling and treating diabetes problems. Numerous researches are ongoing to identify the suitable traditional medical drugs, medicinal herbs, and resources for managing this condition. Murraya koenigii Spreng (family Rutaceae) is commonly known as a ‘curry leaf tree’ locally. It is widely scattered in India and Sri Lanka, and leaves are commonly used for cooking. And also mainly used for various health conditions such as diabetes, anemia, diarrhea, and others. The present review aimed to critically review the anti-hyperglycemic effect of the M. koenigii based on the review, in vitro, in vivo, and clinical studies. Based on this review, the M. koenigii possess flavonoids, phenols, saponins, alkaloids, tannins, and cardiac glycosides. It has shown a potential anti-hyperglycemic effect on induced diabetic rats. This review reported the potential of M. koenigii and its extract to be a high-value dietary product in terms of its anti-hyperglycemic effects and industrial profits. Therefore, the present review supports the researchers and readers/users to realize the importance of using M. koenigii in managing diabetes mellitus. Further, this review provides a valuable document for future scientific-related clinical trials in diabetic patients.